2022
DOI: 10.1186/s12958-022-00964-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response association between maternal pre-pregnancy bodyweight and gestational diabetes mellitus following ART treatment: a population-based cohort study

Abstract: Background The impact of maternal pre-pregnancy bodyweight on gestational diabetes mellitus (GDM) following assisted reproductive technology (ART) treatment has been insufficiently investigated. The aim of this study was to investigate the association between maternal pre-pregnancy bodyweight and GDM following ART. Methods From January 2014 to March 2019, this population-based retrospective cohort study included pregnancies achieved by ART treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…Regarding the potential risk of GDM following ART, Xiong et al reported a linear positive association between pre-pregnancy body weight and the risk of GDM in a population-based cohort study. These findings support the recommendations for pre-pregnancy weight intervention, especially before starting ART procedures [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the potential risk of GDM following ART, Xiong et al reported a linear positive association between pre-pregnancy body weight and the risk of GDM in a population-based cohort study. These findings support the recommendations for pre-pregnancy weight intervention, especially before starting ART procedures [ 20 ].…”
Section: Discussionsupporting
confidence: 85%